Overconfidence and gun preferences: How behavioral biases affect your safety - Fernando G. Cafferata; Patricio Domínguez; Carlos G. Scartascini (Inter-American Development Bank (IDB), 2023)
Overconfidence leads to risky behavior, including when people are around guns. Does overconfidence also shape attitudes about gun ownership and use? We evaluate this possibility by conducting nationally representative surveys in six countries in the Americas, including the United States. Results show that overconfident individuals are more willing to accept the use of guns and more likely to declare their willingness to use guns. These results indicate that overconfidence is a significant behavioral trait correlated with attitudes toward weapons handling, ownership, carrying, and use. Overall, over-confidence could lead, in equilibrium, to lower regulation than optimal and a higher amount of guns, even before considering the effect of the electoral system, lobbying, and campaign contributions. Efforts to correct the biases of individuals confronted with making decisions about guns should be a priority, especially in regulatory contexts. Information about actual performance and the risks entailed by wrong choices is a must. Obliging individuals to reflect on their choices may also help correct observed biases.
Keywords: D91; K40; D72; 330; Overconfidence; Gun attitudes; Gun behavior; Crime; Behavioral biases